Efectos de la aplicación de bioestimulantes después de la roturación del suelo, en el cultivo de banano (musa sp.). - Uyaguari Márquez, Daiser Rafael (Machala : Universidad Técnica de Machala, 2018)
The present work was carried out in the hacienda "La Serrano" owned by Mr. Ab. Ricardo Serrano located in the La Loma canton El Guabo site, the plantation is a Willians banana plantation, of appropriately 20 years of age of the crop, the test area was one hectare, distributed in four treatments including the control, 20 were chosen. plants for each repetition, separated at 10 meters between lots, the maintenance of the plantation was the same for all, two fertilization of Urea plus Potassium Nitrate was made to the whole plantation according to the farm's program. The type of soil in the area was clay loam, with drainages at 1.20 meters and tertiary at 60 cm depth. The bioles were applied with pump CP3 mouthpiece 8015, with approximate discharge of 200 millimeters of volume, with the crown of the plant casts in half moon, the ground previously was made an irrigation two hours before the application to have it in field capacity. The application of the bioles was around the children selected in the plants where the soil was previously broken with the agricultural tool "Hercules", the results of herculizing the soil were carried out in three sites in front of the son of the selected banana plants and the application of the bioles was according to what was indicated in the research as variables; The results of the highest weight of the root mass was for treatment 2 (Humitrex 2kg · ha-1 + Radix 2L · ha-1) with an average weight at the end of the test with 208.3 grams per plant and the control 139 g / pl. The best height was achieved by treatment 2 with 2.88 meters, unlike the witness 2.35 m. For the number of leaves at 30 days after the application I reach T1 (14.33) and the lowest the T4 (12.65), at 60 days the T2 with (16.31) and the lowest T4 ( 14.57M) and at 120 days I reach a total of 18,71 sheets of treatment 2 (Humitrex 2kg · ha-1 + Radix 2L · ha-1), and 17,5 leaves at the end of the trial. The leaf area was calculated using the formula developed by Kened (TLA = L x B x N x 0.80 x 0.662) and the results were for T1 (7.81), T2 (9.20), T3 (7.71) and T4 (7.65) m-2 respectively, for the thickness of the pseudostem at 90 days, the one with the highest value was treatment 2 (Humitrex 2kg · ha-1 + Radix 2L · ha-1), while treatment1 ( (Humitrex 2kg · ha-1), there was no statistical difference, as for the number of hands per cluster it was for T1 (8.1), T2 (9), T3 (8.1) and T4 (8) hands respectively , there being a statistical difference between the T2 (Humitrex 2kg · ha-1 + Radix 2L · ha-1) with the other treatment.In conclusion it was determined that treatment 2 (Humitrex 2kg · ha-1 + Radix 2L · ha-1 ), was the best in terms of all the variables under study, which is recommended to continue shaping these results with other research.
El presente trabajo se realizó en la hacienda “La Serrano” de propiedad del señor Ab. Ricardo Serrano ubicada en el sitio La Loma cantón El Guabo, la plantación es una bananera de variedad Willians, de apropiadamente 20 años de edad del cultivo, el área del ensayo fue de una hectárea, distribuida en cuatro tratamientos incluido el testigo, se escogieron 20 plantas por cada repetición, separadas a 10 metros entre lotes, el mantenimiento de la plantación fue igual para todos, se hicieron dos fertilización de Urea más Nitrato de Potasio a toda la plantación según programa de la hacienda. El tipo de suelo en el área fue franco arcilloso, con drenajes a 1,20 metros y terciario a 60 cm de profundidad. Los bioles fueron aplicados con bomba CP3 boquilla 8015, con descarga aproximada de 200 milímetros de volumen, con la corona de la planta echa en media luna, el suelo previamente se hizo un riego dos horas antes de la aplicación para tenerlo en capacidad de campo. La aplicación de los bioles, fue alrededor de los hijos seleccionados en las plantas donde se roturo previamente el suelo con la herramienta agrícola “Hercules”, los resultados de herculizar el suelo, se realizaron en tres sitios frente al hijo de las plantas de banano seleccionada y la aplicación de los bioles fue de acuerdo a lo indicado en la investigación como variables; Los resultados de mayor peso de la masa radicular fue para el tratamiento 2 (Humitrex 2kg·ha-1 + Radix 2L·ha-1) con un peso promedio al final del ensayo con 208,3 gramos por planta y el testigo 139 g/pl. La mejor altura la alcanzo el tratamiento 2 con 2,88 metros a diferencia del testigo 2, 35 m. Para el número de hojas a los 30 días después de la aplicación lo alcanzo el T1 (14,33) y el menor el T4 (12,65), a los 60 días el T2 con (16,31) y el menor T4 (14,57M) y a los 120 días alcanzo un total de hojas de 18,71 el tratamiento 2 (Humitrex 2kg·ha-1 + Radix 2L·ha-1), y 17,5 hojas al finalizar el ensayo. El área foliar se calculó usando la formula desarrollada por Kened (TLA = L x B x N x 0.80 x 0.662) y los resultados fueron para T1 (7,81), T2 (9,20), T3 (7,71) y T4 (7,65) m-2 respectivamente, para el grosor del pseudotallo a los 90 días el que mayor valor presento fue el tratamiento 2 (Humitrex 2kg·ha-1 + Radix 2L·ha-1), mientras que el tratamiento1 ((Humitrex 2kg·ha-1) testigo no hubo diferencia estadística. En cuanto al número de manos por racimo fue para el T1 (8,1), T2 (9), T3 (8,1) Y T4 (8) manos respectivamente, habiendo una diferencia estadística entre el T2 (Humitrex 2kg·ha-1 + Radix 2L·ha-1) con los demás tratamiento. Como conclusión se determinó que el tratamiento 2 (Humitrex 2kg·ha-1 + Radix 2L·ha-1), fue el mejor en cuanto a todas las variables en estudio, lo que se recomienda seguir conformando estos resultados con otra investigación.
Keywords: HERCULIZAR; BIOLES; SUELO; BANANO